The structure of company ownership and tax avoidance in Indonesia - Rakayana, Wima; Sudarma, Made; Rosidi, Rosidi (International research journal of management, IT and social sciences, 2021)
This study aims to explain the effect of ownership structure (family, government, institutional, foreign, managerial, public) on tax avoidance in Indonesia. This study employed quantitative research with regression analysis, regression method using the annual report on companies listed on the Indonesian stock exchange from the 2017-2019 period with a sample of 93 companies. The tax avoidance was measured using the Cash Effective Tax Rate. The results of this study indicate that the government ownership structure and foreign ownership structure have a positive effect on tax avoidance in Indonesia. Firm size emphasizes the influence of the independent variables on the dependent variable. Family, institutional, managerial, public ownership structures have no influence on tax avoidance. This study indicates that the ownership structure of the company can influence company policy in tax avoidance.